(untitled) (Journal of Hama University, 2022)
Purpose: This study aimed to compare the fracture resistance of different designs of zirconia crowns: Bi-layered zirconia crowns (zirconia core with covered ceramic), monolithic zirconia crowns, and Semimonolithic zirconia crowns . Materials and Methods: The sample consisted of 30 upper incisor zirconia crowns، fixed on metal die،and divided according to the crown design into three groups: the first group: 10 bi-layered zirconia crowns، the second group: 10 monolithic zirconia crowns، the third group: 10 Semimonolithic zirconia crowns. All crowns were cemented by glass ionomer cement،the fracture resistance was studied by the general mechanical testing instrument. Results: mean max load values was(1362.50) N for the first group, (1366.90)N for the second group, and (1742.60)N for the third group،using statistical analyzes, the fracture force of crowns in third group was higher compared to first and second groups, and it was found that there was no statistically significant difference between first and second groups. Conclusions: The design of Semimonolithic zirconia crowns showed the highest fracture resistance compared to the rest of the groups.